Bench thrombolysis and "autotransplantation" as a rescue treatment for venous thrombosis after living‐donor kidney transplantation. (22nd June 2021) - Ghidini, Filippo; De Corti, Federica; Leon, Francesco Fascetti; Trojan, Diletta; Parolin, Mattia; Tognon, Costanza; Castagnetti, Marco; Vidal, Enrico; Gamba, Piergiorgio
Abstract: Background: Allograft venous thrombosis is a severe complication after kidney transplantation (KT). Early diagnosis and prompt treatment are crucial in preserving the survival of the allograft. In this study, we aimed to describe an emergent strategy for the management of acute allograft venous thrombosis. Case presentation: A 4‐year‐old girl, weighing 13.5 kg, was diagnosed with bilateral congenital renal hypodysplasia, urogenital sinus and anorectal malformation. The patient was referred to our department for living‐donor KT. Her mother was eligible as a donor, presenting a body weight ratio of 1:4.5. Thrombosis of the inferior vena cava (ICV) was also identified, without any predisposing factor for thrombophilia. KT was performed by an extraperitoneal approach without complications. Venous anastomosis required a human vascular graft sutured to the ICV, and renal artery was anastomosed to the aorta. On postoperative day (POD) 8, acute abdominal pain and hematuria led to the diagnosis of an allograft venous thrombosis. An emergent laparotomy was required to explant the allograft, followed by bench surgery. The allograft was irrigated with thrombolytic agents and lactated Ringer's solution and then after removing the venous vascular graft, it was reimplanted through vascular anastomosis with the ICV and aorta. The recovery of perfusion and function was good with diuresis since day 4 after re‐surgery. At 2‐year follow‐up, the child presented normal allograft function with an estimated GFR of 65 ml/min/1.73 m 2 . Conclusion: According to our experience, explantation of the kidney allograft, followed by irrigation with thrombolytics in bench surgery, and reimplantation resulted in unexpected optimal outcomes in the case of allograft venous thrombosis.